Food safety issues in international trade: food safety in food security and food trade - Henson, Spencer (International Food Policy Research Institute, 2003)
While not trade measures per se, food safety regulations and standards can impede trade and significantly affect the ability of developing countries to access markets, particularly in industrialized countries. In part, this reflects the growing use of these measures globally in response to the rapid increase in scientific and technical understanding of food-borne hazards to human health. -- from Text